A comparative study of nutrient composition, bioactive properties and phytochemical characteristics of Stauntonia obovatifoliola flesh and pericarp - Li, Rurui; Ru, Yuerong; Feng, Ling; Wang, Zhenxing; He, Xiahong; Zhang, Xuechun (Frontiers in Nutrition, 2022)
A comparative study was conducted among the flesh (SOF) and pericarp (SOP) of Stauntonia obovatifoliola, a wild edible fruit in China. The nutrient composition of both these tissues was first quantified, and liquid-liquid extraction was then used to separate their methanolic extracts to get petroleum ether, chloroform, ethyl acetate, n-butanol, and residual aqueous fractions, which were evaluated for their total phenol content (TPC), total flavonoid content (TFC), antioxidant capacities, and α-glucosidase and acetylcholinesterase inhibition abilities. Finally, high-performance liquid chromatography (HPLC) was used to analyze their phytochemical composition. The results revealed the excellent nutritional properties of both SOF and SOP, especially SOP (total dietary fiber, 15.50 g/100 g; total amino acids, 0.80 g/100 g; vitamin C, 18.00 mg/100 g; Ca, 272.00 mg/kg; K, 402.00 mg/100 g). For both tissues, their ethyl acetate fractions showed the highest TPC (355.12 and 390.99 mg GAE/g DE) and TFC (306.58 and 298.48 mg RE/g DE). Surprisingly, the ethyl acetate fraction of SOP exhibited the strongest DPPH and ABTS radical scavenging capacity with 1046.94 and 1298.64 mg Trolox/g, respectively, which were higher than that of controls Vc and BHT. In contrast, their chloroform fractions exhibited the strongest ferric reducing antioxidant power (1903.05 and 1407.11 mg FeSO4/g DE) and oxygen radical absorbance capacity (951.12 and 1510.21 mg Trolox/g DE). In addition, the ethyl acetate fraction of SOF displayed superior α-glucosidase inhibition ability with the IC50 value of 0.19 mg/mL, which was comparable to control acarbose. In comparison, the ethyl acetate fraction of SOP had the best acetylcholinesterase inhibition ability with the IC50 value of 0.47 mg/mL. The HPLC analysis results demonstrated that the ethyl acetate fraction of SOP showed significantly higher phenolic content, particularly for phenolic acids (p-hydroxybenzoic acid, 8.00 ± 0.65 mg/g) and flavonoids (epicatechin, 28.63 ± 1.26 mg/g), as compared to other samples. The above results suggest that Stauntonia obovatifoliola, especially its pericarp, had excellent nutrient compositions, bioactive properties and phytochemical characteristics, and had the potential to be developed as natural functional food.